A Review of Different Modification Technologies for Dietary Fiber - YOU Yanzhi, SU Cuiyang, ZHANG Liang, LI Jinlong, DING Changhe, QIN Lizhe, CHEN Hua, HU Zhijun (Shipin Kexue, 2025)
As a leading producer of agricultural by-products, China wastes large amounts of resources rich in dietary fiber (DF) every day. Recognized as the “seventh nutrient”, dietary fiber plays a vital role in human health, particularly natural soluble dietary fiber (SDF). Modification technologies to enhance the proportion of SDF in DF and improve its utilization have emerged as a key research focus. This article comprehensively reviews physical, chemical, biological, and combined modification strategies for DF, providing a comparative analysis of their principles. It also summarizes the advantages and limitations of these technologies and discusses future prospects. This review aims to provide a theoretical foundation for the efficient modification of DF. By promoting the high-value transformation of agricultural products, extending the industrial chains, and increasing the added value of products, this review holds significant importance for the sustainable development of agriculture and the advancement of the health food industry.